Production of tantalum nanopowders by electric explosion of wire; Journal of Physics: Conference Series; Vol. 741 : Optoelectronics, Photonics, Engineering and Nanostructures (Saint Petersburg OPEN 2016) - Vlasyuk M. N. Mikhail Nikolaevich (2016, 2016)
Title screen